Study on the effect of koumiss on reactivation of Toxoplasma gondii infection - Yan, Xinlei; Sun, Yufei; Yu, Xiuli; Gao, Jialu; Wang, Hejing; Liang, Ru; Han, Wenying; Jin, Xindong; Guo, Wenhui; Liu, Pufang; Chen, Jia (Frontiers in Nutrition, 2022)
Toxoplasma gondii is an obligate intracellular parasite that infects nucleated cells of all warm-blooded animals, and most patients have latent infections. The latent infection will be reactivated in the immunocompromised or immunocompromised individuals, which will lead to severe toxoplasmosis. At present, less research has been focused on the reactivation of T. gondii infection. Koumiss is a kind of fermented milk made from fresh mare’s milk through natural fermentation that can be applied to clinical and rehabilitation medicine to mitigate the development of various diseases due to its unique functional characteristics. In this study, we explored the antagonistic effect of koumiss on reactivation of T. gondii infection. Mice were treated with dexamethasone to establish a reactivation model after infection with T. gondii and then treated with koumiss. The survival rate, SHIRPA test, serum cytokine levels, organ parasite burden and intestinal microbiota were measured, respectively. Our results showed that koumiss treatment improved the clinical symptoms of mice, significantly reduced the organ parasite burden of mice, and improved the composition and structure of intestinal flora. This study provides new evidence for the alleviation and treatment of toxoplasmosis and provides a novel idea for the development and utilization of koumiss.